Essence of human fredom - "Heidegger, Martin" (London, 2005)
The Essence of Human Freedom is a fundamental text for understanding HeideggerGCOs view of Greek philosophy and its relationship to modern philosophy. These previously untranslated lectures were delivered by Heidegger at the University of Freiburg in the summer of 1930.
Keywords: Philosophy